Studi Komparatif Komisi Penyiaran Indonesia dengan Beberapa Negara (Amerika Serikat, Afrika Selatan, Prancis, Malaysia dan Singapura) - Fadli Zaini Dalimunthe (Nagari Law Review, 2019)
Indonesian Broadcasting Commission or Komisi Penyiaran Indonesia (KPI) is a state institution which is established in 2002 as the implementation of Law on Broadcasting in Indonesia. It has a long history in guarding broadcasting in Indonesia. The research is focused on two problems which are: How the concepts and regulations of the KPI and how the history of this commission in performing its function as the guardian of public right for good and healt broadcasting. This research is related to constitutional regulation and uses both Statute spproach and historical spproach. This article examines the history of KPI formation and compare with similar institutions in some other countries in the world such as United State, South Africa, France, Malaysia and Singapore. By doing a comparison study, it will be able to understand the differences and similarities in order to draw lessons from various countries.